The art of the strain - Abele, Robert; Toro, Guillermo del 1964- (San Rafael, California Insight Editions, 2016)
Based on Guillermo del Toro and Chuck Hogan's best-selling book trilogy, "The Strain" is a high-concept thriller that tells the story of Dr. Ephraim Goodweather (Corey Stoll), the head of the Center for Disease Control Canary Team in New York City. He and his team are called upon to investigate a mysterious viral outbreak with all the hallmarks of an ancient and evil strain of vampirism. As the strain spreads, Eph, his team, and an assembly of everyday New Yorkers battle to control the fate of humanity itself. "The Art of The Strain" delves into the amazing design work that went into creating this chilling TV series, including del Toro's own designs for the menacing beings that pose a threat to humanity's survival. The book also features interviews with key members of the cast and crew and tells the full story of this unique production"--Provided by publisher.
A viral idea -- Incubation -- The art of infection -- The pilot : night zero -- The hunters -- Abraham Setrakian -- Ephriam Goodweather -- Nora Martinez -- Vasiliy Fet -- Dutch Velders -- Gus Elizalde -- A master plan -- The master -- Thomas Eichhorst -- Eldritch Palmer -- Gabriel Bolivar -- The infected -- Vampire biology 101 -- Vamp camp -- Strength in numbers -- Beheadings -- The stinger -- The autopsy -- It spreads -- Season two -- Casting forward -- The feelers -- Master transfer -- Light reading -- Conclusion.
Keywords: Strain (Television program).; Television broadcasting -- Special effects